Strategic Climate Litigation before National Courts: Can European Union Law be used as a Shield? - Christina Eckes (German Law Journal)
The climate emergency is unfolding. Efforts to reduced greenhouse gas emissions globally, including the efforts of the European Union and the Member States, are severely insufficient to hold global warming below the 1.5°C temperature limit. In light of this public institutional failure, civil society actors increasingly resort to strategic climate litigation. However, the EU has very restrictive standing requirements for direct actions against general acts. Therefore, most strategic climate litigation is brought to national courts. In 2023 and 2024, national judges have in several cases allowed defendant states to use EU law as a shield against the litigants’ demands to declare national climate targets and policies insufficient. This Article argues that in light of the fact that EU climate policy is inadequate and nearly impossible to challenge, it is highly problematic when national judges accept EU law to be an obstacle to (full) judicial review. First, EU law itself is not an obstacle to judicial review of national climate policy. Second, the European Convention on Human Rights, read in light of KlimaSeniorinnen, imposes higher requirements on Member States than EU law. Third, the European Court of Human Rights would not accept the “EU law as a shield” argument.